Relación entre funcionamiento familiar y síntomas depresivos en una población adolescentes escolarizados de los departamentos de Córdoba y La Guajira
This study explores the connection between family functioning and depressive symptoms in school-aged adolescents from the departments of Córdoba and La Guajira, Colombia. Using a quantitative, non-experimental, descriptive, and cross-sectional design, it investigates how family dynamics impact the mental health of these young people. Data were collected using the Center for Epidemiological Studies Depression Scale (CES-D) and the Family APGAR, which provide a detailed view of different dimensions of family functioning and their relationship with depressive symptoms.